تأثير درجات الحرارة والرطوبة النسبية على ديناميكية جماعات ذبابة الفاكهة Ceratitis capitata Wiedmann على الحمضيات في منطقة اللاذقية (Latakia University Journal -Biological Sciences Series, 2018)
The research carried out in the village of Sarsakia in the Lattakia region, about 1 hectare of citrus, within an orchard planted with different varietis of citrus, all orchards surrounding the field planted with citrus. Five of McPhail Traps, which contain (Femilure) a new pheromone attractive to females of C. capitata were distributed on citrus trees in the study area on 4/6/2016 and the traps readings were taken weekly until 3/6/2017. The attractant replaced after 18 weeks. We put a digital (thermometer - humidity) in the search site, and recorded the temperature and humidity minimum and maximum weekly. The results of  McPhail Traps indicated a decrease in the number of flies during the summer months of June, July and August (picking of late varieties), returning to activity  in autumn   from mid-September (the beginning of the citrus season) to reach a peak from late October to November (Available fruits and appropriate conditions), to return and disappear suddenly in the winter from the beginning of December (a severe decrease in temperature to approximately 0 Cْ) until the beginning of June next year. The temperature  had a low correlative correlation r = 0.199 and moisture had a very low inverse correlation r = -0.0282.   نُفِّذَ البحث في قرية السرسكية ضمن منطقة اللاذقية، على مساحة 1 هكتار تقريباً، ضمن بستان مزروع بأنواع وأصناف مختلفة من الحمضيات، جميع البساتين المحيطة بالحقل مزروعة بالحمضيات. وزعت 5 مصائد ماكفيل تحوي كل مصيدة على Femilure (جاذب لإناث ذبابة الفاكهة) على الأشجار في موقع الدراسة بتاريخ 2016/6/4 وأُخِذت قراءات دورية أسبوعية لغاية 2017/6/3، واستبدل فرمون الفيميلور كل 18 أسبوع، كما وُضِع ميزان (حرارة - رطوبة) رقمي في موقع البحث، وسُجِّلت درجات الحرارة و الرطوبة الدنيا و العليا أسبوعياً. أشارت نتائج مصائد ماكفيل إلى تناقص أعداد ذبابة الفاكهة في بيئة الحمضيات خلال أشهر الصيف حزيران وتموز وآب (قطف الأصناف المتأخرة)، لتعود للنشاط خريفاً من أواسط أيلول (بداية موسم الحمضيات) ولتبلغ ذروتها من أواخر شهر تشرين الأول حتى تشرين الثاني(الثمار متوفرة والظروف البيئية ملائمة)، لتعود وتختفي فجأة ً شتاءً بداية من كانون الأول (انخفاض شديد بالحرارة لما يقارب 0 سْ) حتى بداية حزيران العام التالي. وجدنا ارتباط طردي ضعيف للحرارة مع تغير أعداد الإناث الملتقطة r=0.199، وكان للرطوبة ارتباط عكسي ضعيف جداً r=-0.0282.